Advances on CMOS Shift Registers for Digital Data Storage - Mohammad Arif Sobhan Bhuiyan; Hasrul Nisham Bin Rosly; Mamun bin Ibne Reaz; Khairun Nisa Minhad; Hafizah Husain (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The shift register is the heart of the current digital data storage system. Current trends of wireless device designs are to balance the power consumption, cost and portability of the device. The worldwide research is giving emphasize on increasing the amount of memory at minimum possible space to reduce the overall size of the devices now a days. This paper reports a detailed survey on different types of shift registers in CMOS technology from the performance, design and application point of view. It also discusses the technologies available for the design of shift registers with their merits and demerits. This survey will act as a reference for the scientists to design the high-performance memory module. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5207